The Effect of Service Information System Quality on the Intensity of Use of Digital Learning Service Systems - Amra, Amra; Ibrahim, Muh. Akmal; Susanti, Gita; Pauzi, Rizal (Departemen Ilmu Administrasi FISIP UNHAS, 2022)
Information systems are used by organizations to help the organization's operations become more efficient in their role as a tool to win the competition. Data processing has become an important part of the Management Information System that will affect every organization's activities. Universitas Hasanuddin's management information system has developed an online information system through the website, namely the Learning Management System. The Universitas Hasanuddin Learning Management System is prepared to support and expedite the learning process. However, the current learning management system has not been understood by lecturers and students due to poorly understood features, slow system access, and a lack of socialization of the use of the learning management system at the department or study program level, so that it does not encourage lecturers and students to use it more often. Learning Management System. This study aims to determine how the system's quality significantly affects the intensity of use. This type of quantitative descriptive research uses a survey approach in this study. The respondents in this study were adjusted for lecturers with a sample of 100 people and students with a sample of 100 people. Data collection techniques included Questionnaires and Document Studies. Data analysis techniques using Structural Equation Modeling will be processed using AMOS software version 24.00. This study found that the effect of system quality on the intensity of use resulted in a cr value of 0.328 < 1.96 and a p-value of 0.74 > 0.05, so there was no significant effect of system quality on the intensity of use. This answers the hypothesis in the study. Namely, H0 is rejected, and H1 is accepted.